Autonomic correlates of attachment insecurity in a sample of women with eating disorders - Dias, Pedro (2011)
This study examined associations between attachment insecurity and autonomic response during the Adult Attachment Interview (AAI) in a sample of 47 women with eating disorders using a new system for the synchronous acquisition of behavioral and physiological data: the Bio Dual-channel and Representation of Attachment Multimedia System (BioDReAMS; Soares, Cunha, Zhan Jian Li, Pinho, & Neves, 1998). Consistent with the emerging literature on the psychophysiology of adult attachment, insecurity was positively correlated with electrodermal reactivity during the AAI. Furthermore, relatively secure patients showed some evidence of parasympathetic withdrawal, which can be conceptualized as evidence of more effective emotion regulation. Results suggest that, even among women with diagnosed psychopathology, security is associated with more productive patterns of psychophysiological response to attachment-related challenges.